Epidemiological and laboratory features of acute enteric infections (Bangladesh Journal of Medical Science, 2021)
Background: This work describes etiological structure and statistics for causes of acute enteric infections and salmonellosis in modern conditions.Method: It was analyzed the common epidemiologic signs and indices of modern acute enteric infections (AEI), caused by opportunistic microorganisms (OMO), various viruses and salmonella.Result: The research also shows the integrative intoxication indicators of causal groups in endogenous intoxication which point to these phenomena being caused by autointoxication at the moment of one’s own cells disruption as well as induced by bacterial endo- and exotoxins.Conclusion: The work compares the etiology of AEI on the basis of reviewing their epidemiological attributes, changes in the integrative indication for endogenous intoxication, as well as vectors and causal correlations between hematological and microbiotic indicators.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.748-755